2022
DOI: 10.18585/inabj.v14i1.1772
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thymoquinone Administration on Local Immunoglobulin-G Levels of Rattus norvegicus Strain Wistar Sciatic Nerve Crush Injury Model

Abstract: BACKGROUND: Immunoglobulin-G (IgG) is a product of the initial response to secondary immune response, which accumulates in distal segment of the nerve after crush injury. Thymoquinone modulates the adaptive immune response. Effect of thymoquinone administration on local IgG levels of Rattus norvegicus Wistar rats sciatic nerve crush injury model has not been elucidated.METHODS: This was an experimental study, with 63 Rattus norvegicus Wistar rats that divided into 9 groups. Three groups were given placebo, 3 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…(18) Our earlier study showed that crush-injured rats treated with thymoquinone significantly decreased local IgG antibody levels. (19) A study previously employed 100 mg/kg of thymoquinone as a successful oral dosage in a Wistar rat model of neuropathic pain. (20) Another study indicated that the maximal oral intake of thymoquinone for rats of both genders is 250 mg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…(18) Our earlier study showed that crush-injured rats treated with thymoquinone significantly decreased local IgG antibody levels. (19) A study previously employed 100 mg/kg of thymoquinone as a successful oral dosage in a Wistar rat model of neuropathic pain. (20) Another study indicated that the maximal oral intake of thymoquinone for rats of both genders is 250 mg/kg.…”
Section: Introductionmentioning
confidence: 99%